1997
DOI: 10.1002/(sici)1096-8628(19970211)68:4<466::aid-ajmg19>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of malformations in the axial skeleton in human trisomy 21 fetuses

Abstract: In the present study, we analyzed the development of the axial skeleton in human trisomy 21 fetuses and defined the fields in the axial skeleton affected in this form of aneuploidy. We investigated 31 human fetuses with trisomy 21, gestational ages 12-24 weeks, on the basis of radiographs of midsagittal tissue blocks of the axial skeleton, comprising the cranial base and the spine. Malformation or agenesis of the nasal bone was present in 19 of 31 fetuses. Nineteen cases had vertebral malformations. Fourteen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 21 publications
(29 reference statements)
5
71
0
2
Order By: Relevance
“…The frequency and the character of the malformations seen in triploidy differed markedly from those reported in trisomies [Kjaer et al, 1996Keeling et al, 1997]. The most consistent type of axial skeletal malformation in the triploid fetuses was fusion of adjacent vertebral corpora seen in 6 fetuses.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The frequency and the character of the malformations seen in triploidy differed markedly from those reported in trisomies [Kjaer et al, 1996Keeling et al, 1997]. The most consistent type of axial skeletal malformation in the triploid fetuses was fusion of adjacent vertebral corpora seen in 6 fetuses.…”
Section: Discussionmentioning
confidence: 75%
“…The following 7 osseous axial regions or fields were analyzed: the sacral, lumbar, thoracic, and cervical vertebral segments of the spine, the basilar part of the occipital bone, the postsphenoid component of the sphenoid bone of the cranial base, and the nasal bones. These fields were defined in earlier studies on trisomy 18, 21, and 13 [Kjaer et al, 1996Keeling et al, 1997]. …”
Section: Methodsmentioning
confidence: 99%
“…The establishment of the appendicular skeleton begins early in prenatal development and continues through adolescence, and previous studies in humans have shown that individuals with trisomy have altered bone development both pre- and postnatally [8, 9]. Prenatal evidence suggesting changes in DS bone development has been derived from ultrasound measurements of the long bones [10].…”
Section: Introductionmentioning
confidence: 99%
“…The 2nd trimester axial skeleton in fetuses with trisomy 13 was not studied previously, although such studies were made in trisomy 18 and trisomy 21 Keeling et al, 1997]. Axial skeletal analysis in trisomy 13 demonstrates characteristic abnormalities in the lumbosacral spine, sphenoid, and nasal bones.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the fetal axial skeleton in trisomy 18 and trisomy 21 showed that different fields were affected Keeling et al, 1997]. Therefore it seemed appropriate to investigate the axial skeleton in trisomy 13.…”
Section: Introductionmentioning
confidence: 99%